Outcomes of surgical treatment of non-metastatic gastric cancer in patients aged 70 and older: A systematic review and meta-analysis. Issue 9 (September 2022) - Argillander, T.E.; Festen, S.; van der Zaag-Loonen, H.J.; de Graeff, P.; van der Zaag, E.S.; van Leeuwen, B.L.; Nagengast, W.B.; Verhage, R.J.J.; Ruurda, J.P.; van Munster, B.C.; van Duijvendijk, P.
Abstract: The optimal surgical treatment strategy for gastric cancer in older patients needs to be carefully evaluated due to increased vulnerability of older patients. We performed a database search for randomized controlled trials (RCTs) and cohort studies that included patients ≥70 years with potentially resectable stage I-III gastric cancer. Postoperative and survival outcomes were compared between groups undergoing 1) gastrectomy vs conservative treatment (best supportive care or non-operative treatment), 2) minimally invasive (MIG) vs open gastrectomy (OG), or 3) extended vs limited lymphadenectomy. When possible, results were pooled using risk ratios (RR). Thirty-one studies were included. Six retrospective studies compared overall survival (OS) between gastrectomy (N = 2332) and conservative treatment (N = 246). Longer OS was reported in the gastrectomy group in all studies, but study quality was low and meta-analysis was not feasible. Eighteen cohort studies compared MIG (N = 3626) and OG (N = 5193). MIG was associated with fewer complications (pooled RR 0.68, 95% confidence interval 0.54–0.84). OS was not different between the groups. Two RCTs and five cohort studies compared outcomes between extended (N = 709) and limited lymphadenectomy (N = 1323). Complication rates were comparable between the groups. Two cohort studies found longer OS or cancer-specific survival after extended lymphadenectomy. No quality of life (QoL) or functional outcomes were reported. In older patients with gastric cancer, there is low-quality evidence for better OS after gastrectomy vs conservative treatment. Compared to OG, MIG was associated with less postoperative morbidity. The evidence to support extended lymphadenectomy is limited. QoL and functional outcomes should be addressed in future studies.